Contrasting ecophysiology of two widespread arid zone tree species with differing access to water resources. (June 2018) - Nolan, Rachael H.; Tarin, Tonantzin; Rumman, Rizwana; Cleverly, James; Fairweather, Kendal A.; Zolfaghar, Sepideh; Santini, Nadia S.; O'Grady, Anthony P.; Eamus, Derek
Abstract: Arid environments can support the seemingly unlikely coexistence of species tolerant of, or sensitive to, dry soil moisture. Here, we examine water-use and carbon-gain traits in two widespread tree species in central Australia: Acacia aptaneura and Eucalyptus camaldulensis . The former has a shallow root distribution and relies on soil moisture, while the latter is groundwater dependent. We hypothesised that A. aptaneura would exhibit a suite of characteristics that confer tolerance to low soil moisture, in contrast to E. camaldulensis . Consistent with our hypotheses A. aptaneura was relatively more anisohydric than E. camaldulensis (seasonal leaf water potential of −7.2 to −0.8 MPa cf . −1.4 to −0.3 MPa). Additionally, compared to E. camaldulensis, A. aptaneura had lower water potential at turgor loss (−2.5 cf . −1.1 MPa); a larger Huber value; smaller, narrower and thicker phyllodes/leaves; and larger photosynthetic capacity ( J max ); and larger water-use efficiency. Further, water-use efficiency for E. camaldulensis was similar to species receiving annual rainfall of 1500 mm, despite annual rainfall of 348 mm. We conclude that mean annual rainfall is the dominant determinant of water and carbon relations for A. aptaneura, but not E. camaldulensis . This has important implications for ecosystem-scale transpiration and primary productivity across this arid zone. Highlights: We measured water and carbon-related traits in two contrasting species. Eucalyptus camaldulensis is groundwater-dependent, unlike Acacia aptaneura. Both tree species are distributed across arid and semi-arid Australia. A. aptaneura exhibited anisohydric behaviour and large photosynthetic capacity. Water-use efficiency in E. camaldulensis was similar to mesic-zone species.